Authors' Response. - Hall, Mary; Padua, David; Pingali, Keshav (Communications of the ACM, 2009)
A response by Mary Hall, David Padua, and Keshav Pingali to a letter to the editor about their article “Compiler Research: The Next 50 Years” in the February 2009 issue is presented.